Induction of alpha-synuclein pathology in the enteric nervous system of the rat and non-human primate results in gastrointestinal dysmotility and transient CNS pathology - Manfredsson, Fredric P.; Luk, Kelvin C.; Benskey, Matthew J.; Gezer, Aysegul; Garcia, Joanna; Kuhn, Nathan C.; Sandoval, Ivette M.; Patterson, Joseph R.; O'Mara, Alana; Yonkers, Reid; Kordower, Jeffrey H. (Neurobiology of disease, 2018)
Alpha-Synuclein (α-syn) is by far the most highly vetted pathogenic and therapeutic target in Parkinson's disease. Aggregated α-syn is present in sporadic Parkinson's disease, both in the central nervous system (CNS) and peripheral nervous system (PNS). The enteric division of the PNS is of particular interest because 1) gastric dysfunction is a key clinical manifestation of Parkinson's disease, and 2) Lewy pathology in myenteric and submucosal neurons of the enteric nervous system (ENS) has been referred to as stage zero in the Braak pathological staging of Parkinson's disease. The presence of Lewy pathology in the ENS and the fact that patients often experience enteric dysfunction before the onset of motor symptoms has led to the hypothesis that α-syn pathology starts in the periphery, after which it spreads to the CNS via interconnected neural pathways. Here we sought to directly test this hypothesis in rodents and non-human primates (NHP) using two distinct models of α-syn pathology: the α-syn viral overexpression model and the preformed fibril (PFF) model. Subjects (rat and NHP) received targeted enteric injections of PFFs or adeno-associated virus overexpressing the Parkinson's disease associated A53T α-syn mutant. Rats were evaluated for colonic motility monthly and sacrificed at 1, 6, or 12 months, whereas NHPs were sacrificed 12 months following inoculation, after which the time course and spread of pathology was examined in all animals. Rats exhibited a transient GI phenotype that resolved after four months. Minor α-syn pathology was observed in the brainstem (dorsal motor nucleus of the vagus and locus coeruleus) 1 month after PFF injections; however, no pathology was observed at later time points (nor in saline or monomer treated animals). Similarly, a histopathological analysis of the NHP brains revealed no pathology despite the presence of robust α-syn pathology throughout the ENS which persisted for the entirety of the study (12 months). Our study shows that induction of α-syn pathology in the ENS is sufficient to induce GI dysfunction. Moreover, our data suggest that sustained spread of α-syn pathology from the periphery to the CNS and subsequent propagation is a rare event, and that the presence of enteric α-syn pathology and dysfunction may represent an epiphenomenon. •α-syn pathology was induced in the enteric nervous system of both rodents and non-human primates.•Enteric α-syn pathology correlates with decreased gastrointestinal motility.•Induction of α-syn pathology in the ENS in the colon correlates with transient α-syn pathology in the brainstem.•Induction of enteric α-syn pathology is not sufficient to produce sustained brain pathology.•Enteric α-syn pathology may be an epiphenomenon in Parkinson's disease.